The indirect effect from childhood maltreatment to PTSD symptoms via thought suppression and cognitive reappraisal. (April 2021) - Sistad, Rebecca E.; Simons, Raluca M.; Mojallal, Mahsa; Simons, Jeffrey S.
Highlights: Childhood maltreatment was associated with PTSD symptoms directly, as well as indirectly via cognitive reappraisal. Thought suppression was directly associated with PTSD symptoms. The overall indirect effect from childhood maltreatment on PTSD via thought suppression was not significant. Negative affect was directly and indirectly associated with PTSD symptoms, via both cognitive appraisal and thought suppression. The present study demonstrates the significant indirect effect from childhood maltreatment to PTSD symptoms via cognitive reappraisal and underscores the robust association between thought suppression and PTSD symptoms. Abstract: Background: Emotion regulation strategies may help explain the risk of experiencing posttraumatic stress disorder (PTSD) symptoms among adults with a history of child maltreatment. However, no study to date has examined the roles of both thought suppression and cognitive reappraisal in the association between childhood maltreatment and PTSD symptoms. Objective: The current study sought to understand the associations between childhood maltreatment, thought suppression, cognitive reappraisal, and PTSD symptoms while controlling for negative affect and gender. Participants and setting: Data were collected on 660 university students (71 % female) ages 18–25 between 2013 and 2014. Participants completed self-report measures of childhood maltreatment, PTSD symptoms, and emotion regulation strategies. Method: A structural equation model was tested to examine the direct and indirect effects from childhood maltreatment to PTSD symptoms via thought suppression and cognitive reappraisal, over and above gender and negative affect. Results: Childhood maltreatment was directly associated with PTSD symptoms ( β = 0.28, SE = 0.04, p < .001). Childhood maltreatment also had a significant indirect effect on PTSD via cognitive reappraisal ( β = 0.01, CI 95 % [0.00, 0.03]), but not through thought suppression, although ( β = 0.01, CI 95 % [−0.00, 0.04]) thought suppression was significantly positively associated with PTSD symptoms ( β = 0.21, SE = 0.04, p < .001). Conclusion: The present study sheds light on the effect of childhood maltreatment and two commonly used emotion regulation strategies on PTSD symptoms.